2017
DOI: 10.1097/brs.0000000000001772
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Perioperative Low-Dose Ketamine Does Not Improve Short and Long-term Outcomes After Pediatric Idiopathic Scoliosis Surgery

Abstract: 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 40 publications
3
23
0
Order By: Relevance
“…This finding is consistent with our results from a previous randomized placebo-controlled trial, where ketamine administered in the intraoperative and postoperative periods did not yield an opioid-sparing effect in adolescents with scoliosis undergoing spinal fusion 11. Interestingly, a more recent trial and a new meta-analysis12 also showed lack of beneficial effect of ketamine in postoperative pain 27. It is important to note that one limitation of the most recent study in adolescents undergoing spinal fusion27 as well as ours11 is that neither study examined the effect of ketamine on chronic postsurgery pain.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with our results from a previous randomized placebo-controlled trial, where ketamine administered in the intraoperative and postoperative periods did not yield an opioid-sparing effect in adolescents with scoliosis undergoing spinal fusion 11. Interestingly, a more recent trial and a new meta-analysis12 also showed lack of beneficial effect of ketamine in postoperative pain 27. It is important to note that one limitation of the most recent study in adolescents undergoing spinal fusion27 as well as ours11 is that neither study examined the effect of ketamine on chronic postsurgery pain.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, a more recent trial and a new meta-analysis12 also showed lack of beneficial effect of ketamine in postoperative pain 27. It is important to note that one limitation of the most recent study in adolescents undergoing spinal fusion27 as well as ours11 is that neither study examined the effect of ketamine on chronic postsurgery pain. Nevertheless, our findings from the present study are discrepant to those showing that low-dose ketamine infusion during the perioperative period yields opioid-sparing effects in adults undergoing major surgeries 28.…”
Section: Discussionmentioning
confidence: 99%
“…This supported previous data for scoliosis repair, that low-dose ketamine intraoperatively did not prevent remifentanil-induced AOT postoperatively 9. Furthermore, Perelló et al 13 studied a 72-hour course of low-dose ketamine to assess both short-term outcomes of postoperative morphine utilization, adverse side effects, as well as long-term outcomes with incidence of persistent postsurgical pain at 6 months postoperatively. While these three studies did not support ketamine use, Jabbour et al 12 demonstrated that when magnesium was added to ketamine, opioid consumption was reduced.…”
Section: Discussionsupporting
confidence: 84%
“… 32 However, in a recent small study of 48 pediatric patients undergoing scoliosis spine surgery, a subanesthetic ketamine dose of 0.5 mg/kg followed by an infusion at 0.12 mg/kg per hour for 72 hours yielded no significant differences in opioid consumption or pain scores compared with placebo. 33 In a longitudinal cohort study performed in 230 children, adolescents, and young adults, patients with acute (78%) and chronic (22%) pain were given different doses of ketamine infusions depending on whether they were opioid tolerant. Opioid-naive patients were administered ketamine infusions of 0.05 to 0.4 mg/kg per hour, opioid-tolerant patients received dosages ranging from 0.05 to 1 mg/kg per hour, and those with documented opioid-induced hyperalgesia underwent infusion rates of 1 mg/kg per hour.…”
Section: Discussionmentioning
confidence: 99%